2012
DOI: 10.1007/s11002-012-9212-3
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity endorsers' performance on the “ground” and on the “floor”

Abstract: This article analyzes the relationship between two types of performances, one on the ground (of a tennis court) and the other on the floor (of the stock market). The empirical application looks into the tennis player, Rafael Nadal, and his endorsing firms. The findings show a positive reaction in the market value when the tennis player wins matches in the Grand Slams, the intriguing effect being the diminishing sensitivity pattern that such reaction shows and the absence of loss aversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Despite some likely exposure for runners-up during the event, as well as some media coverage ex post, the endorsed firm's shares did not exhibit significant returns, neither on a market-adjusted basis nor on a risk-adjusted basis. These findings are in line with those of Nicolau and Santa-María (2013). Ngan et al (2011) experimentally studied purchase intentions for endorsed brands for sports teams and found that winning (as opposed to losing) an event leads to the strongest purchase intentions.…”
Section: Empirical Analysissupporting
confidence: 82%
See 4 more Smart Citations
“…Despite some likely exposure for runners-up during the event, as well as some media coverage ex post, the endorsed firm's shares did not exhibit significant returns, neither on a market-adjusted basis nor on a risk-adjusted basis. These findings are in line with those of Nicolau and Santa-María (2013). Ngan et al (2011) experimentally studied purchase intentions for endorsed brands for sports teams and found that winning (as opposed to losing) an event leads to the strongest purchase intentions.…”
Section: Empirical Analysissupporting
confidence: 82%
“…We make a distinction between returns for endorsed clothing brands and equipment brands. Compared to previous research (e.g., Farrell et al 2000;Nicolau and Santa-María 2013), one of our contributions is the inclusion of non-superstars. We defined a superstar based on the world ranking in the week previous to the start of the tournament.…”
Section: Regression Modelsmentioning
confidence: 99%
See 3 more Smart Citations